Hurricanes, tsunamis, and other natural disasters - Langley, Andrew; McGuire(3,(BBills (Boston Kingfisher, 2006)
Stunning photographs help take readers into the world of natural disasters
Restless Earth -- Volcanoes -- Storm and flood -- Drought and disease
Includes extra Web sites, book lists and places to explore--Cover
Includes bibliographical references and index
11
Keywords: Hurricanes -- Juvenile literature; Hurricanes; Natural disasters -- Juvenile literature; Natural disasters; Tsunamis -- Juvenile literature; Tsunamis